2022
DOI: 10.1001/jamanetworkopen.2021.43151
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Outcomes, and Severity Risk Factors Associated With SARS-CoV-2 Infection Among Children in the US National COVID Cohort Collaborative

Abstract: IMPORTANCEUnderstanding of SARS-CoV-2 infection in US children has been limited by the lack of large, multicenter studies with granular data. OBJECTIVE To examine the characteristics, changes over time, outcomes, and severity risk factors of children with SARS-CoV-2 within the National COVID Cohort Collaborative (N3C). DESIGN, SETTING, AND PARTICIPANTS A prospective cohort study of encounters with end dates before September 24, 2021, was conducted at 56 N3C facilities throughout the US. Participants included c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 36 publications
10
100
0
2
Order By: Relevance
“…The N3C Data Enclave, data transfer from sites to N3C, and this analysis were approved under separate institutional review board protocols as documented elsewhere. The N3C Data Enclave is approved under the authority of the National Institutes of Health Institutional Review Board. Each participating N3C site maintains an institutional review board–approved data transfer agreement.…”
Section: Methodsmentioning
confidence: 99%
“…The N3C Data Enclave, data transfer from sites to N3C, and this analysis were approved under separate institutional review board protocols as documented elsewhere. The N3C Data Enclave is approved under the authority of the National Institutes of Health Institutional Review Board. Each participating N3C site maintains an institutional review board–approved data transfer agreement.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in a large US cohort study, Martin et al. (2021) observed that there were differences in demographic characteristics and pre-existing comorbidities between severity subgroups wherein marginalized populations (e.g., Black/African American race), being younger than 12 years, and having a pediatric complex chronic condition were predictive of peak disease severity ( 98 ). These results may suggest that early identification of children likely to progress to severe disease could be achieved using key data elements, and may help in the treatment of pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obese children were at higher odds of hospitalization (overall and in the ICU), although this was of limited statistical significance. Yet, in studies from high-income countries, obesity has been consistently demonstrated as a risk factor for disease severity in children, especially in adolescents ( 15 , 36 ). In animal studies, angiotensin-converting enzyme 2 (ACE2) protects against SARS-CoV-2 associated acute respiratory distress syndrome (ARDS) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%